“Gestión ecoeficiente de los residuos plásticos de la zona urbana en la parroquia Velasco Ibarra del cantón el empalme” - Alava Andrade, Lady Vanessa (2020)
This research work is based on the management of plastic waste in the urban area of the Velasco Ibarra parish, El Empalme canton, taking into consideration the excessive pollution by plastics in nearby ecosystems, the exorbitant environmental impact generated by the dump open of the commonwealth to which the canton belongs and the benefits of recycling plastics in the country. For the development of this work, real and updated primary data were taken as a reference such as field trips, surveys and interviews using a sample of 382 people, as well as documents and institutional reports as a secondary source, it was necessary to analyze and contrast said information obtained for the correct elaboration of eco-efficient waste management indicators in the parish and in this way it can serve as a reference for future research and projects to be implemented regarding the use of plastic waste. To obtain the results, interviews were conducted with municipal staff from the waste management department, owners of recyclers, population surveys and weighing of plastic waste for three weeks to a representative sample of the parish, obtaining a per capita generation of 0, 77 kg of plastic weekly per household, the urgent need to implement recycling programs in the area was identified because 90% of the population agrees to separate plastic waste at the source, as well as greater dissemination, socialization and compliance with municipal ordinances since 66% of the population says they do not know the existence of these and according to the cluster analysis it is related to the population that when the collecting vehicle does not pass it burns, buries it or dumps it into water bodies, it is concluded that as strategy should generate agreements between the GADM of the Canton and the recycling and processing companies of plastics for the approval disposal of this waste, extend the useful life of the sanitary landfill, lower management costs, minimize environmental impacts and even generate employment for the recycling sector. KEY WORDS: Waste, recycling, plastics, management, eco-efficient